2021
DOI: 10.1016/j.chest.2020.09.246
|View full text |Cite
|
Sign up to set email alerts
|

Operational Recommendations for Scarce Resource Allocation in a Public Health Crisis

Abstract: The COVID-19 pandemic may require rationing of various medical resources if demand exceeds supply. Theoretical frameworks for resource allocation have provided much needed ethical guidance but hospitals still need to address objective practicalities and legal vetting to operationalize scarce resource allocation schemata. To develop operational scarce resource allocation processes for public health catastrophes, including the COVID-19 pandemic, five health systems in Maryland formed a consortium – wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The triage team constitutes only one component of a broader process of scarce resource allocation and processes upstream and downstream of triage team decisions that will also impact feasibility, effectiveness, and fairness of the system overall (21). Our prior work supports the efficiency of collecting patient information items from an institutional electronic health record (22), but local planning within each institution for how to collect this information will be important to support operationalizability.…”
Section: Discussionmentioning
confidence: 99%
“…The triage team constitutes only one component of a broader process of scarce resource allocation and processes upstream and downstream of triage team decisions that will also impact feasibility, effectiveness, and fairness of the system overall (21). Our prior work supports the efficiency of collecting patient information items from an institutional electronic health record (22), but local planning within each institution for how to collect this information will be important to support operationalizability.…”
Section: Discussionmentioning
confidence: 99%
“…As an objective measure of clinical course, nSOFA score has a potential utility both as a proxy variable for disease severity and as a risk assessment indicator for short-and long-term clinical endpoints [9]. In this study, the nSOFA score showed good correlation in most cases and its ndings will be useful for clinicians and researchers who need tools to objectively measure the risk of death, as well as for healthcare leaders and policy makers who develop resource allocation protocols for critically ill patients [24].…”
Section: Discussionmentioning
confidence: 73%
“…Hansson et al [27] reported that AA patients with CRP <60 g/L, WBC <12 × 10 9 /L, and age <60 years could be treated conservatively with 89% accuracy [21]. The management algorithms of emergency disease have changed during Cov19 [28,29]. The management of acute appendicitis involves, if possible, conservative treatment as an outpatient, short hospitalization, operation with an open technique and under regional anesthesia [16].…”
Section: Discussionmentioning
confidence: 99%